1994
DOI: 10.21273/horttech.4.3.275
|View full text |Cite
|
Sign up to set email alerts
|

A Brushing Apparatus for Height Control of Bedding Plants

Abstract: Height control for vegetable transplants has become challenging with the loss of the industry standard growth regulator, daminozide (Alar). One alternative to growth regulators—brushing—was conducted on two cultivars of Lycopersicon esculentum Mill. Five weeks of brushing twice daily resulted in height suppression for both tomato cultivars. Brushing treatments were performed successfully by use of a grower-designed apparatus constructed from readily available materials. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Brushing does not damage tomato transplants if treatments are applied carefully. In fact, brushing often improves tomato transplant appearance (Latimer and Thomas, 1991;Schnelle et al, 1994); we found a more uniform canopy and a better ability to maintain that appearance when the flats were transported.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Brushing does not damage tomato transplants if treatments are applied carefully. In fact, brushing often improves tomato transplant appearance (Latimer and Thomas, 1991;Schnelle et al, 1994); we found a more uniform canopy and a better ability to maintain that appearance when the flats were transported.…”
Section: Discussionmentioning
confidence: 65%
“…It may be advantageous to delay the beginning of treatment, either to limit the amount of handling of the plants or because the plants are growing on schedule. In earlier experiments using mechanical stimulation to control tomato transplant height, brushing was begun at the cotyledon stage (Baden and Latimer, 1991;Latimer and Thomas, 1991;Schnelle et al, 1994). Our experiments show that it is not necessary to begin treatments at such an early stage.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This moveable system is mobile, set on castors and has a size of dimensions of about 6 × 5 feet with adjustable working height and width. Brushing of tomato seedlings were performed by pulling a four-bar apparatus across the tomato seedlings several times [94]. In yet another interesting case-study, various herbs (Basil, coriander, mint) were mechanically stimulated in production house style green-house with a machine using light clothes attached to an irrigation boom continuously for 108 times per day.…”
Section: Automation Of Ms Treatment For Potential Benefitsmentioning
confidence: 99%
“…Taken together, it is not surprising that researchers have created devices to automatically stimulate plants through brushing [27,32,38], or vibration (see [6] for several examples). However, these efforts have not been taken up widely due to technical limitations of the systems in question [6,35].…”
Section: Plants Touch and Technologymentioning
confidence: 99%